2020
DOI: 10.1007/s11739-020-02562-2
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of noninvasive positive pressure ventilation in the treatment of COVID-19-associated acute hypoxemic respiratory failure: a single center, non-ICU setting experience

Abstract: The role of noninvasive positive pressure ventilation (NIPPV) in COVID-19 patients with acute hypoxemic respiratory failure (AHRF) is uncertain, as no direct evidence exists to support NIPPV use in such patients. We retrospectively assessed the effectiveness and safety of NIPPV in a cohort of COVID-19 patients consecutively admitted to the COVID-19 general wards of a medium-size Italian hospital, from March 6 to May 7, 2020. Healthcare workers (HCWs) caring for COVID-19 patients were monitored, undergoing naso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
39
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(42 citation statements)
references
References 30 publications
2
39
0
1
Order By: Relevance
“…Mortality in patients treated with CPAP ranged from 14-24% [252,256,264,265,268,271] to 43-55% [254,260], although possibly reaching 84% when CPAP was the ceiling treatment [276]. Mortality in patients treated with NIV was reported in five studies and ranged from 5% to 52% (but reaching 86% in DNI patients) [261,263,269,272,274]. Pooling outcomes for the CPAP and NIV groups, Avdeev and colleagues estimated a mortality of 23% [255], and Bellani and colleagues estimated a mortality of 25% [270], while pooled results from Burns et al reported a 50% mortality among DNI patients [257].…”
Section: Recommendationsmentioning
confidence: 99%
“…Mortality in patients treated with CPAP ranged from 14-24% [252,256,264,265,268,271] to 43-55% [254,260], although possibly reaching 84% when CPAP was the ceiling treatment [276]. Mortality in patients treated with NIV was reported in five studies and ranged from 5% to 52% (but reaching 86% in DNI patients) [261,263,269,272,274]. Pooling outcomes for the CPAP and NIV groups, Avdeev and colleagues estimated a mortality of 23% [255], and Bellani and colleagues estimated a mortality of 25% [270], while pooled results from Burns et al reported a 50% mortality among DNI patients [257].…”
Section: Recommendationsmentioning
confidence: 99%
“…Recent experience in COVID-19 related Acute respiratory failure (21 publications including 1553 patients) 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 with HFNC, CPAP and Bi-Level Ventilation (using negative pressure rooms in only one series 15 ) shows average success of 60%, 55% and 59%, respectively, and an average infection rate in health professionals of 5.2%, less than the 12% reported in New York City among the staff not necessarily working with NIRT. 28 …”
mentioning
confidence: 99%
“…Time to IMV was similar in survivors and deceased patients. Moreover, casualties in RICU were not reported and in-hospital mortality was lower than previously described 5 , 6 , supporting strategy safeness.…”
mentioning
confidence: 54%